Assessment of Entrepreneurial Stress Based on Gender - Latha, G.; ., . (International Journal of Engineering and Technology, 2018)
Entrepreneurs are the backbone in the economic development and employment of any country. Every country organizes many assistance and training programs to develop their skills and potential. But entrepreneurs face several barriers and problems. Stress is one of the major problems faced by them.Â In this paper an attempt has been made to analyze stress of entrepreneurs based on gender. Self imposed deadlines and quotas, feeling hurried and pressurized without time, feeling themselves as competitive, ambitious and achievement oriented are the potential sources of stress. Proper planning skills, time management skills are essential for entrepreneurs.Â Â